ELASTICITY OF CORN PRICE TRANSMISION AND ITS IMPLICATION TO FARMERS - Ahmad Muslim (Universitas Islam Indonesia, 2011)
Corn has important roles to Indonesian economy both for staple foods and for price transmission to other products. The high domestic demand for corn compared to its domestic production has made corn imports continue to grow. This research is aimed to know the elasticity of price transmission and its implication to corn’s farmers. The results of analysis show that corn price transmission is inelastic. The coefficient shows that corn market is oligopsony under the imperfect competition market. To help the corn farmers, the government has to provide fertilizer subsidy and farm credit with low interest rates, as well as impose import tariff on corn. Keywords: Corn, Elasticity of price transmission, oligopsony, imperfect competition marketJEL classification numbers: Q00, Q12, Q18